POSTCOLONIAL THEORIES ON PROMOTING WORLD ENGLISH IN EFL SPEAKING CLASSES - Desy Rizki Lukitasari (UIN Alauddin Makassar, 2020)
English, as one colonial’s legacy, is a lingua franca. It connects people with different first languages and cultures around the world. As the demand of 21st century learning, the learning of English in EFL speaking classes has changed. It no longer focuses on how to speak like native speakers, but to speak like an educated person; to speak in English confidently and fluently, demonstrating good grammar and correct pronunciation. Therefore, World English with different accents and dialects exist. Furthermore, to explain the nature of English which is the result of Western dominaton during colonialism and imperialism, Postcolonial theories can explain the significance of World English in EFL speaking classes. This library research, then, aims to answer this research question: ‘How do postcolonial theories contribute significances to the use of the World English in EFL speaking classes?’. From the theoretical analysis employed from experts, important figures, and previous prominent theories and findings on discussing the same topic, there are two postcolonial theories which contribute to the existence of the World English in today’s EFL speaking classes. First, English Linguistic Imperialism which influenced the Other, East, or Orient to feel it was compulsory to speak in English like natives in the past. Second, Bhabha’s hybridity and Fanon’s cultural resistance which help to give an understanding about accepting mixed cultures and identity. Finally, the discussion of the study will raise an awareness of how Postcolonial theories relate to the presence of the World English used by non-native English speakers and give an insight to EFL learners and practitioners about the World English in speaking classes.